Meningkatkan Hasil Belajar Dengan Penggunaan Media Peta Pada Materi Pengetahuan Dasar Pemetaaan Siswa Kelas X IPS-2 SMAN 1 Wangi-Wangi - Dewi, Chindy Citra; Surdin, Surdin; Amaluddin, La Ode (UNIVERSITAS NEGERI MAKASSAR, 2019)
SMAN 1 Wangi-Wangi is one of the schools in Wakatobi Regency which is the location of research because the learning outcomes are still low. The purpose of this study is(1) To find out student learning activities by using map media on basic knowledge mapping materials. (2) To find out the teaching activities of teachers by using map media on basic knowledge mapping materials.(3) To find out the geography learning outcomes of students of cl ass X IPS-2 of SMA Negeri 1 Wangi-Wangi by using map media on mapping basic knowledge material. This research is a classroom action research (CAR) and the data of this study using activity observation sheets that contain student learning activities and teacher teaching activities, while to obtain student geography learning outcomes by conducting tests as a research method.From the results of the study showed that: (1) student learning activities obtained an average score of 3.5 which is categorized as good.(2) teacher teaching activities obtained an average score of 3.4 which is categorized as good. (3) the geography learning outcomes of students of class X IPS-2 SMAN 1 obtained an average score of 79, with 81% completeness or there were 26 students from 32 students with a value of â‰¥ 70 according to the KKM of geography subjects.So, it can be concluded that after the implementation of cycle 1 and cycle 2 by using map media on student learning activities, teacher teaching activities, and student learning outcomes have increased.SMAN 1 Wangi-Wangi is one of the schools in Wakatobi Regency which is the location of research because the learning outcomes are still low. The purpose of this study is(1) To find out student learning activities by using map media on basic knowledge mapping materials. (2) To find out the teaching activities of teachers by using map media on basic knowledge mapping materials.(3) To find out the geography learning outcomes of students of cl ass X IPS-2 of SMA Negeri 1 Wangi-Wangi by using map media on mapping basic knowledge material. This research is a classroom action research (CAR) and the data of this study using activity observation sheets that contain student learning activities and teacher teaching activities, while to obtain student geography learning outcomes by conducting tests as a research method.From the results of the study showed that: (1) student learning activities obtained an average score of 3.5 which is categorized as good.(2) teacher teaching activities obtained an average score of 3.4 which is categorized as good. (3) the geography learning outcomes of students of class X IPS-2 SMAN 1 obtained an average score of 79, with 81% completeness or there were 26 students from 32 students with a value of â‰¥ 70 according to the KKM of geography subjects.So, it can be concluded that after the implementation of cycle 1 and cycle 2 by using map media on student learning activities, teacher teaching activities, and student learning outcomes have increased.